POINT PREVALENCE OF HAEMONCHOSIS IN SHEEP AND GOATS SLAUGHTERED AT MULTAN ABATTOIR - M. A. Raza; S. Murtaza; H. A. Bachaya; G. Dastager; A. Hussain (Journal of Animal and Plant Sciences, 2009)
The present study was conducted to determine the prevalence of Haemonchus (H.) contortus in slaughtered sheep and goats at Multan abattoir. A total of 4740 animals were slaughtered and examined from 21 January 2007 to 20 February 2007 in Multan abattoir. In case of sheep, 793 out of 2133 were positive and prevalence of H. contortus infestation was 37.18% while 811 out of 2607 (31-10%) goats were positive. Sex wise prevalence of H. contortus in sheep was 34.11% (291/853) in male and 39.22% (502/1280) in female while in goats prevalence in male was 29.91% (312/1043) and in female was 31.90% (499/1564).
Keywords: Point Prevalence; Haemonchus contortus; a nematode